Flexural and interlaminar shear response of novel methylmethacrylate composites reinforced with high-performance fibres - Aswani Kumar Bandaru; Jayaram R. Pothnis; Alexandre Portela; Raghavendra Gujjala; Hong Ma; Ronan M. O'Higgins (Polymer Testing)
This experimental work presents a comparative study on the mechanical behaviour of novel infusible methylmethacrylate matrix (Elium®) composites reinforced with different types of high-performance fibres. A vacuum-assisted resin infusion process was employed to fabricate the laminates using carbon, basalt, Kevlar®, and high molecular weight polyethene (UHMWPE) fibres. Flexural and interlaminar shear properties of the composites were evaluated. Test results revealed that carbon fibre composites had superior flexural strength, stiffness and interlaminar shear stress as compared to the other composites tested. Further, composites containing Kevlar and UHMWPE fibres demonstrated significantly higher flexural strains to failure. Post-testing, specimens were examined using scanning electron microscopy (SEM). Microscopy revealed possible interfacial interaction differences based on the reinforcement fibre type, which was further confirmed by an analytical approach for analysing the flexural behaviour of various types of composites. The sequence of damage progression in specimens was also analysed.